Analysis of Information Governance Principal Implementation in the Management Information System of Indonesian Botanical Gardens’ Plant Collections Data (Makoyana) - Heri Apriyanto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
Information and data are the new gold in the last decade. The value of information and data has risen since the popularity of the internet. The Internet provides a possibility to exchange information and data without depending on place and time. However, it also opens the possibility of illegal access to the information and misused data and information practices. To solve the issue, the implementation of information governance is needed in the organization or the IT project. One of the essential aspects of information governance is an information security and privacy. It can prevent the leak of information for illegal purposes. Information governance provides a set of policies to control and manage information. The Management Information System of Indonesian Botanical Gardens’ Plant Collection Data (Makoyana) contains valuable information about flora biodiversity in Indonesia. Information on flora biodiversity can be an asset for the Indonesian government that affect some sectors such as politics, economics, laws, and society. For instance, information about a specific flora can be used to develop a new product for cosmetics, medicines, or other purposes that have a positive impact on economics. The implementation of information governance is essential to managing the information and data in the Makoyana project. This research will analyze the implementation of information governance principles in the Makoyana project. Some information governance principles theories will be used to assess the project such as from ARMA international, Smallwood, and Sedona Conference.